2015
DOI: 10.1002/jobm.201400664
|View full text |Cite
|
Sign up to set email alerts
|

Directed evolution of a β‐1,3‐1,4‐glucanase from Bacillus subtilis MA139 for improving thermal stability and other characteristics

Abstract: In order to improve some characteristics of a β-1,3-1,4-glucanase from Bacillus subtilis MA139, directed evolution was conducted in this study. After error-prone PCR, the β-1,3-1,4-glucanase gene, glu-opt, was cloned into the vector pBGP1 and transformed into Pichia pastoris X-33 to construct a mutant library. Three variants named as 7-32, 7-87, and 7-115 were screened from 8000 colonies. Amino-acid sequence analysis showed that these mutants had one or two amino-acid substitutions (7-32: T113S, 7-87: M44V/N53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 50 publications
(73 reference statements)
2
2
0
Order By: Relevance
“…In contrast with these results some investigators reported an inhibitory effect of Co ++ ions on β-1,3–1,4-glucanase (Chaari et al 2012 ; Elgharbi et al 2013 ; Chaari et al 2014 ; Wang et al 2014 ; Elgharbi et al 2017 ; Ali et al 2019 ). The enzyme was also slightly activated in presence of Mn ++ , this result agreed with the data reported by (Teng et al 2007 ; Kim et al 2014 ; Yan et al 2018 ), while disagreed with (Wang et al 2007 ; Apiraksakorn et al 2008 ; Hong et al 2009 ; Luo et al 2014 ; Pei et al 2015 ; Gao 2016 ) who reported partial inhibition effect of Mn ++ ions while complete inhibition of the enzyme was reported by (Yang et al 2008 ; Elgharbi et al 2013 ; Chaari et al 2014 ; Kim et al 2014 ; Elgharbi et al 2017 ).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…In contrast with these results some investigators reported an inhibitory effect of Co ++ ions on β-1,3–1,4-glucanase (Chaari et al 2012 ; Elgharbi et al 2013 ; Chaari et al 2014 ; Wang et al 2014 ; Elgharbi et al 2017 ; Ali et al 2019 ). The enzyme was also slightly activated in presence of Mn ++ , this result agreed with the data reported by (Teng et al 2007 ; Kim et al 2014 ; Yan et al 2018 ), while disagreed with (Wang et al 2007 ; Apiraksakorn et al 2008 ; Hong et al 2009 ; Luo et al 2014 ; Pei et al 2015 ; Gao 2016 ) who reported partial inhibition effect of Mn ++ ions while complete inhibition of the enzyme was reported by (Yang et al 2008 ; Elgharbi et al 2013 ; Chaari et al 2014 ; Kim et al 2014 ; Elgharbi et al 2017 ).…”
Section: Discussionsupporting
confidence: 77%
“…Partial inhibition of the enzyme occurred by high concentration of Ca ++ , while no change in activity observed with low level, similarly to these data slight inhibition with Ca ++ ions was reported by Apiraksakorn et al ( 2008 ), Elgharbi et al ( 2013 ) and Wang et al ( 2014 ) and dissimilarly Ca ++ ions made activation for other β-1,3–1,4-glucanases (Gao 2016 ; Elgharbi et al 2017 ; Bernardi et al 2018 ). Complete inhibition of Halomonas meridiana ES021 β-1,3–1,4-glucanase was also observed with Cu ++ ions, similarly to Yang et al ( 2008 ), Elgharbi et al ( 2013 ) and Pei et al ( 2015 ), this was disagreed with the activating effect reported by Celestino et al ( 2006 ), Wang et al ( 2007 ), Yang et al ( 2014 ) and Niu et al ( 2016b ) for the same metal ion. Urea slightly inhibited the enzyme activity, similar result was reported by Wang et al ( 2007 ).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations